Sting Nematode, Belonolaimus longicaudatus Rau (Nematoda: Secernentea: Tylenchida: Tylenchina: Belonolaimidae: Belonolaiminae) - William T. Crow; Angela S. Brammer (EDIS)
Sting nematodes are among the most destructive plant-parasitic nematodes on a wide range of plants. Adults can reach lengths greater than 3 mm, making them one of the largest plant-parasitic nematodes. While there are several species of sting nematodes described, only Belonolaimus longicaudatus Rau is known to cause widespread crop damage. This document is EENY-239, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2001.